Internet-Mediated Interreligious Dialogue A Study Case on @KatolikG’s Model of Dialogue - Martinus Joko Lelono (Journal of Asian Orientation in Theology, 2021)
Internet-mediated interreligious relations could go in two directions: increasing the number of interreligious encountering with weakening process of religious exclusivism and lead people to religious fundamentalism and interreligious polarization. In the Indonesian context, the emergence of the Garis Lucu (Funny line) social media platforms allow a dialogical internet-mediated interreligious relation rather than the monologue one. This opportunity especially works in the relation between @KatolikG and @NUGarisllucu, two (unofficial) religious-based social media account that cover Twitter, Instagram, and Facebook Page. This study uses @KatolikG perspective on looking for several patterns of internet-mediated interreligious dialogue. The study finds three patterns of internet-mediated interreligious dialogue: doing daily dialogue, discussing sensitive issues, and doing social actions. Within these three works, @KatolikG contributes in sharing communal agenda and concerns that enable people to work hand in hand in supporting interreligious dialogue. Following the idea of Pope Francis to have ‘a greater discernment and responsibility for contents both sent and received,’ @KatolikG supports social cohesion among Indonesians in the context of Internet-Mediated Interreligious Dialogue.